SPE Improved Oil Recovery Conference 2020
DOI: 10.2118/200432-ms
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolamine as Alkali for Alkali Surfactant Polymer Flooding - Development of a Low-Complexity Field Implementation Concept

Abstract: A successful pilot in the Marmul field in the south of the Sultanate of Oman used a formulation consisting of 2% sodium carbonate, 0.3% surfactant, and 0.27% polymer. Marmul crude oil has a high total acid number (TAN = 0.9 mg KOH/ml). The petroleum acids are neutralized by alkali to form soaps which mix with the added surfactant to generate low interfacial tension (IFT) between oil and brine. For a commercial scale chemical-flood the quantity of sodium carbonate that needs to be transported is very large. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Alkali-polymer injection is a promising technology to increase oil recovery in fields containing reactive oils. The initially generated soaps of the alkali with the reactive components of the oil can be measured to determine the amount of soap generated as a function of pH and the minimum required alkali concentration [22]. IFT measurements and phase behavior tests can be used to evaluate the presence of stable Windsor III emulsions (e.g., [23,24]) or thermodynamically instable emulsions (e.g., [9,25,26]) and the presence of salt-crude oil complexes at high alkali concentrations which are detrimental for enhanced oil recovery [27].…”
Section: Discussionmentioning
confidence: 99%
“…Alkali-polymer injection is a promising technology to increase oil recovery in fields containing reactive oils. The initially generated soaps of the alkali with the reactive components of the oil can be measured to determine the amount of soap generated as a function of pH and the minimum required alkali concentration [22]. IFT measurements and phase behavior tests can be used to evaluate the presence of stable Windsor III emulsions (e.g., [23,24]) or thermodynamically instable emulsions (e.g., [9,25,26]) and the presence of salt-crude oil complexes at high alkali concentrations which are detrimental for enhanced oil recovery [27].…”
Section: Discussionmentioning
confidence: 99%
“…Crude oil with high acidity (acid number) can be suitable for ASP flooding [29]. For efficient ASP flooding, a reduced amount of alkali is used for a high acid number of crude oil [30]. The emulsification effect and viscosity enhancement make ASP flooding more effective [31].…”
Section: Alkaline-surfactant-polymer (Asp) Floodingmentioning
confidence: 99%
“…The data are summarized in Table 1. The TAN number of the oil amounts to 5.67 mg KOH/g and the saponifiable acids around 116 µmol/g, as determined by the method described by Southwick et al [28], shown in Figure 1 and measured by soap generated by titration at a given pH for the 10-ML crude Polymers 2024, 16, 854 3 of 25 oil. For experimental application, a mixture was used in order to match the reservoir viscosity, 100 mPa•s at 35 • C, using 10-ML oil + 4% cyclohexane.…”
mentioning
confidence: 99%